2013
DOI: 10.1210/jc.2012-3289
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Accumulation During Lipid Overfeeding Is Related to Subcutaneous Adipose Tissue Characteristics in Healthy Men

Abstract: Characteristics of sc adipose tissue appear therefore to contribute to the development of visceral fat depot, supporting the adipose tissue expandability theory and extending it to early stages of weight gain in nonobese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 24 publications
6
67
0
Order By: Relevance
“…Interestingly, testosterone has been shown to downregulate lipoprotein lipase, which stimulates release of free fatty acids contributing to systemic insulin resistance, in abdominal subcutaneous tissue (31). Moreover, the protective capacity to store excess energy in subcutaneous tissue may be genetically regulated, and diacylglycerol O-acyltransferase 2, mechanistically implicated in this differential storage, is regulated by androgens (32,33). Indeed, exceeding the capacity of the subcutaneous compartment, acting as a cardiometabolic protective 'sink', may lead to spillover of fat into ectopic sites such as intraabdominal, intramuscular, intrahepatic or even perivascular compartments which may contribute to insulin resistance (34,35,36).…”
Section: Effects Of Adt On Body Composition and Insulin Resistancementioning
confidence: 99%
“…Interestingly, testosterone has been shown to downregulate lipoprotein lipase, which stimulates release of free fatty acids contributing to systemic insulin resistance, in abdominal subcutaneous tissue (31). Moreover, the protective capacity to store excess energy in subcutaneous tissue may be genetically regulated, and diacylglycerol O-acyltransferase 2, mechanistically implicated in this differential storage, is regulated by androgens (32,33). Indeed, exceeding the capacity of the subcutaneous compartment, acting as a cardiometabolic protective 'sink', may lead to spillover of fat into ectopic sites such as intraabdominal, intramuscular, intrahepatic or even perivascular compartments which may contribute to insulin resistance (34,35,36).…”
Section: Effects Of Adt On Body Composition and Insulin Resistancementioning
confidence: 99%
“…Previous work has also demonstrated that weight cycling is associated with metabolic syndrome (9, 10), although this finding was not replicated in our data, possibly owing to limited follow-up of body mass assessments over the 8 years. Several overfeeding studies have demonstrated that healthy obese adults display different biological responses to moderate weight gain, such as increased adipose tissue capacity for lipogenesis (11) and favourable characteristics of subcutaneous adipose tissue that help prevent visceral fat depots (12). Thus, more subtle differences in metabolic function that were not possible to measure in this study may differentiate stable and unstable healthy obesity.…”
Section: Discussionmentioning
confidence: 86%
“…We powered our study based on previous studies involving high-fat-diet-induced body mass gain in humans (21)(22)(23). With 20 subjects, 80% power and alpha 5 0.05 we anticipated being able to detect a 1.0 kg (Cohen's d 5 1.2) difference in the magnitude of change in body fat mass in VSL#3 compared with control following the high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty healthy, non-obese (BMI <30 kg m 22 ) males (18-30 years of age) volunteered to participate in this study. All participants were healthy and not taking any medications that might impact the dependent variables.…”
Section: Methods Participantsmentioning
confidence: 99%